An experimental investigation on slicing of potassium dihydrogen phosphate (KDP) crystal - Wang, Q. G.; Gao, H.; Pei, Zhijian J.; Guo, D. M.; Teng, X. J. (My University, 2013)
Because of its unique properties, potassium dihydrogen phosphate (KDP) crystals are widely used for electro-optical applications. Slicing is needed to make KDP crystal lens with desired shapes. However, reported studies on slicing of KDP crystal are scarce. This paper presents an experimental investigation on slicing of KDP crystals. Output parameters studied include surface roughness, flatness error, parallelism error, and subsurface damage. Effects of wire sawing input variables (feed rate and diamond grit size) on output parameters are investigated. Comparisons of wire sawing and band sawing are also made.
Keywords: Flatness error; KDP crystal; Slicing; Subsurface damage; Surface quality; Wire sawing